Investigation of Adsorption Process of Hydrogen on Fe-Ti: Theoretical Simulation and Interpretation of Isotherms with Statistical Physics Treatment - Manaa, Marwa Ben; Hachicha, Mohamed Abdennaceur; Schmaltz, Bruno; Abdelmottaleb, Ben Lamine (My University, 2017)
Three theoretical expressions for the adsorption isotherms of hydrogen on Fe-Ti at three temperatures 100 K, 80 K and 60 K have been established. Our objective in this modeling is to select the adequate model that presents a high correlation with the experimental curves. The establishment of these new expressions is based on statistical physics formalism. This method has allowed the estimation of physicochemical parameters in the theoretical model. The parameters intervening in the adsorption process have been deduced directly from experimental adsorption isotherms by numerical simulation. We will mainly introduce three main parameters affecting the adsorption process, namely: the density of hydrogen receptor sites Nm, the number of molecules per site n and the pressure at half saturation P1 which characterizes the binding between the hydrogen and receptor sites on Fe-Ti. Then we apply the model to calculate the internal energies in an isothermal transformation, an isobaric transformation and an isosteric transformation.
Keywords: Hydrogen; Statistical physics; Adsorption isotherm; Internal energy; Monolayer model